ZVZCS Based High Frequency Link Grid Connected SVM applied Three Phase Three Level Diode Clamped Inverter for Photovoltaic Applications Part-II - Soumyadeep Ray; Madichetty Sreedhar; Abhijit Dasgupta (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
This article proposes a newly proposed highly effective Zero Voltage and Zero Current switching based Front end converter with a High Frequency Transformer with a Three Phase Three Level Diode Clamped Inverter in photovoltaic applications. The switching scheme is implemented in MATLAB/ Simulink condition. ZVZCS condition is achieved. This type of converter shows high efficiency and very negligible switching loss. Finally ZVZCS based High Frequency Link Diode Clamped Inverter is connected to Grid. An MCI optimized Current controller is used with SVM switching technique.  In This article, responses with three types of controllers (I, PI, PID) have been examined and compared. Simulation results show the effectiveness, and validity of this technique.DOI: http://dx.doi.org/10.11591/ijpeds.v5i1.5411